MEANS OF RECOVERING WORKING CAPACITY FOR RUNNERS ON MEDIUM AND LONG DISTANCES (Physical Culture and Sport: Scientific Perspective, 2024)
The article examines the issue of the integrated use of pedagogical and medical-biological means of recovery of working capacity in the training of runners for medium and long distances. The analysis of scientific and methodical literature showed that optimization of the training process is impossible without effective use of means of restoring the working capacity of athletes. After all, insufficient recovery during training cycles, excessive physical exertion, a large number of competitions, not a rational construction of training, unsatisfactory nutrition, etc. negatively affect the performance of athletes.Summarized modern data on the effectiveness of the use of pedagogical means of recovery in the process of training runners: 1) compensatory work (flexibility exercises, sports games, cycling, swimming in the pool, slow running, etc.); 2) active recreation; 3) classes with small and medium loads after classes with large loads, which differ in orientation; 4) compliance of the load with the capabilities of the athletes; 5) rationally constructed warm-up and the final part of training; 6) restorative microcycles in macrocycles and annual preparation cycles; 7) rationally structured training, micro-, meso- and macrocycles.The effectiveness of the use of extra-training medical and biological (physical) means of recovery in the training of runners has been revealed: sports massage, sauna, hydro-, electro-procedures and light irradiation, depending on the volume and intensity of the load in microcycles. Schemes of medical and biological means of restoring the performance of runners in the preparatory and competitive periods of the annual training cycle are presented. Nutrition was analyzed as a means of replenishing the energy expenditure of runners. The ratio of proteins (14-15%), fats (25%) and carbohydrates (60-61%) in the diet of athletes is shown. The importance of maintaining water balance, consumption of vitamins, mineral supplements, and sports drinks in the training of track and field athletes is revealed.
Keywords: recovery of working capacity; medical and biological means; pedagogical means; middle- and long-distance runners; track and field athletics; sports training